75.2k views
1 vote
(08.03)A set of equations is given below:

Equation H: y = −x + 2
Equation J: y = 3x − 4

Which of the following steps can be used to find the solution to the set of equations?
−x = 3x − 4
−x +2 = 3x
−x + 2 = 3x − 4
−x + 1 = 3x + 2

User KG Sosa
by
6.3k points

1 Answer

1 vote

Answer: Third option


-x + 2 = 3x - 4.

Explanation:

One of the ways of solving a system of equations is by equating the equations and solving for one of the variables.

In this case we have the system:


y = -x + 2\\\\y = 3x - 4

Note that if
y is equal
-x + 2 and also
y equals
3x - 4

Then logically
-x + 2 must be equal to
3x - 4.

We write equality.


-x + 2 = 3x - 4.

Then the correct answer is the third option.

We can also solve for the variable x


-4x = -6\\\\4x = 6\\\\x = (6)/(4)\\\\x = (3)/(2)

User Faisal Ahmed
by
5.8k points